Cobalt-containing hexagonal mesoporous molecular sieves (Co-HMS): Synthesis, characterization and catalytic activity in the oxidation reaction of ethylbenzene - Bhoware, Shrikant S.; Shylesh, S.; Kamble, K. R.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2006)
Cobalt-containing hexagonal mesoporous materials (Co-HMS and Co/HMS) with different cobalt content were synthesized for the first time by direct hydrothermal and post-synthesis (grafting) method. The materials were characterized in detail by X-ray diffraction, BET surface area, N-2 sorption isotherms, SEM, TEM, UV-vis and XPS techniques. Powder X-ray diffraction pattern, N2 adsorption-desorption analysis and TEM analysis show the presence of hexagonal mesoporous structure, having Type W isotherms and reveals the typical wormhole-like morphology. Spectroscopic techniques like UV-vis and XPS reveal cobalt in +2 oxidation state and tetrahedrally coordinated. Liquid phase oxidation of ethylbenzene using TBHP (70 wt%) as an oxidant shows that the catalysts are highly active, under solvent free conditions as well as under lower cobalt concentrations. Leaching studies performed by hot filtration experiments show that the cobalt catalysts prepared by hydrothermal methods are stable, while the grafted catalysts show the leaching of cobalt under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Co-HMS; ethylbenzene; HMS; hydrothermal; Oxidation

Oxidation of ethyl benzene and diphenyl methane over ordered mesoporous M-MCM-41 (M = Ti, V, Cr): synthesis, characterization and structure-activity correlations - Jha, Ratnesh Kumar; Shylesh, S.; Bhoware, Shrikant S.; Singh, A. P. (Microporous and Mesoporous Materials, 2006)
Transition metals (M = Ti, V, Cr) were incorporated into the MCM-41 framework by surfactant-assisted direct hydrothermal (DHT) methods and were characterized in detail by XRD, N-2 adsorption-desorption, TG-DTG/DTA, SEM/TEM, DR UV-Vis, XPS and EPR. The structural regularity as well as the textural properties of the M-MCM-41 materials was confirmed by XRD, TEM and adsorption-desorption techniques. Nature of metal species and the percentage of framework as well as extra framework metal sites in the MCM-41 matrix are discussed in detail by various spectroscopic techniques. The catalytic activity as well as the selectivity of the M-MCM-41 catalysts were explored in the one-step liquid-phase oxidation reaction of ethyl benzene and diphenyl methane. Reaction data showed that the oxidation activity is more when H2O2 was used an oxidant, acetonitrile as solvent and V-MCM-41 as catalyst. However, the selectivity towards the desired keto derivatives (ethyl benzene to acetophenone and diphenyl methane to benzophenone) follows the order, Ti-MCM-41 > V-MCM-41 > Cr-MCM-41. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: diphenyl methane; Ethyl benzene; MCM-41; Oxidation

Characterization and catalytic activity of cobalt containing MCM-41 prepared by direct hydrothermal, grafting and immobilization methods - Bhoware, Shrikant S.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
{Cobalt containing hexagonal mesoporous molecular sieves (MCM-41) were prepared by different methods viz., direct hydrothermal synthesis, grafting and immobilization. The calcined material was characterized by various spectroscopic tools such as powder X-ray diffraction (XRD), N-2 adsorption-desorption isotherms, Fourier transformed infra-red (Fr-IR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), diffuse reflectance UV-vis and X-ray photoelectron spectroscopy (XPS). The XRD patterns show the highly intense (100) reflection peak in the range 2-3 degrees (2 theta angle), characteristic of mesoporous material. Higher order reflection peaks suggest highly ordered mesoporous structure. N2 adsorption-desorption isotherms are of type IV according to IUPAC classification and the steep rise in the isotherms in the narrow range 3.5-4.5 of relative pressure (P/P-0) is due to the condensation of N-2 gas molecules in the pores (characteristic of mesoporous structure). In FT-IR increase in the intensity of band at 960 cm(-1) with the increase of the cobalt content in Co-MCM-41 samples indicate the incorporation of cobalt ions in the framework of MCM-41. SEM and TEM reveal spherical morphology for the cobalt substituted MCM-41. UV-vis spectra demonstrate the characteristic features of framework and extraframework cobalt in MCM-41. Cobalt is in +2 oxidation state as evidenced from UV-vis and XPS. The catalysts were tested for the side chain oxidation of ethylbenzene using 70 wt.% tert-butyl hydrogen peroxide as an oxidant with and without the use of solvent. Solvents have effect in the catalytic activity and selectivity. In the absence of solvent, substituted cobalt [
Keywords: 2-butanol; cyclohexanone; Mesoporous molecular sieves; MPV reduction

Catalytic activity of cobalt containing MCM-41 and HMS in liquid phase oxidation of diphenylmethane - Bhoware, Shrikant S.; Kamble, K. R.; Singh, A. P. (Catalysis Letters, 2009)
Cobalt containing MCM-41 and HMS were synthesized by direct hydrothermal (DHT) and post synthesis methods (grafting and immobilization). The catalytic activity of these materials was investigated in the liquid phase oxidation of diphenylmethane at 80 A degrees C with TBHP (70 wt%) as oxidant. Comparative study of cobalt containing MCM-41 and HMS was carried out to reveal the catalytic performance of framework, extraframework and immobilized cobalt species. The role of the solvent in the performance of catalyst was examined with different polar and non polar solvents. Oxidation of diphenylmethane in solvent free media (under similar reaction conditions) shows formation of hydroxy derivatives of benzophenone in addition to main product (benzophenone). Hundred percent selectivity to benzophenone was obtained when the reaction was carried out in solvent.
Keywords: diphenylmethane; HMS; Immobilization; MCM-41; XRD